Fulfillment of The Right to Protection Guarantee for Witnesses and Victims of Crime in Indonesia - Lailatul Masrurah; Ali Ridwan; Iskandar Iskandar (Definisi: Jurnal Agama dan Sosial Humaniora, 2022)
Because the testimony of witnesses and victims is the primary evidence in criminal law, the rules and regulations control how witnesses and victims' rights are to be fulfilled. Victims-as-witnesses have rights guaranteed by law, but in practice, these rights are seldom honored by authorities, and many witnesses are subjected to threats and intimidation from the offender, my family, and even law enforcement officials. As a result, the protection of witnesses and victims' rights becomes a concern. Using the legal definition of a witness, as well as the rights and duties of victims who serve as witnesses, this paper examines how Indonesian courts ensure the rights of witnesses and victims are upheld. Qualitative research is utilized in the study of normative law. Legal documents of both major and secondary importance are used as the basis for this research. To be a witness, a person must fulfill the formal and material standards, and must have personal knowledge of the events they are reporting. Physical and psychological security from threats and intimidation as well as monthly pay for traveling expenses are among the rights given by the law against witnesses. In many laws and regulations, particular provisions are included for the protection of victim-witness rights. Keywords: Rights, Witnesses, Victims